Plate VII: Chlorophyceæ - Whipple, George Chandler (The Microscopy of Drinking Water, 1914)
Illustrated plate depicting various forms of chlorophyceæ (green algae), microscopic plant organisms living in water. The magnification of the organisms depicted on the plate varies from 100 to 500 diameters.
Keywords: Scientific illustration; Microscopy; Microorganisms; Green algae; Water--Analysis